Recovery of gold and mercury from the tailings of amalgamation process from the artesanal mining - Aramburú Rojas, Vidal Sixto (2010)
The sample which is the subject of this research work is the process of amalgamation tailings, from the district of Lomas, department of the Piura. Provided by the miners in the area. The mineralogical characterization of the samples showed the presence of the following minerals: gold, electrum, pyrite, arsenopyrite, hematite, goethite and ganges. Tests were conducted metallurgical concentrator Falcon to different forces of gravity: 40, 50, 60, 70 and 80 G’s, with a particle size of 56.55% - 200 mesh. Metallurgical balances indicate that the best evidence is gathered with 60 G’s, obtaining a concentration of 82.78 g/TC, recovery of 17.76% and 28.55 radio concentration. The results indicate that these teams mostly work as preconcentration. The head trial of this amalgamation tailings is 18.69 g/TC gold and 4.62 ppm of mercury, the average calculated heads is 16.16 g/ TC gold and 3.64 ppm of mercury, the difference of these heads is by the presence of free gold and electrum as shown in characterization. One of the important aspects of the study is that mercury in the tailings of the Falcon concentrator has an average grade of 3.67 ppm. This indicator is very high compared with the maximum permissible limits which is 0.14 ppm. Combined tests were also conducted Falcon and cyanide concentration in the sample remolida to a particle size of 77.89% - 200 mesh. The result indicates the Falcon concentrator quality gold concentrate 137.19 g/TC, recovery of 19.54% and 46.51 concentrate radio. The cyanidation of tailings from the concentrator Falcon is favorable, leading to a recovery of 97.56% gold with cyanide consumption of 1.64 Kg/TM and 9.44 Kg/TM of lime. It is important to mention that the cyanidation tailings is 2.70 ppm mercury.